Composite using ECC-steel wire to strengthen RC beams: Flexural performance and FEM analysis - Wei Yang; Xiaoqing Xu; Zhigang Zhang; Dawei Liu; Huilin Hu; Dagmawi Getahun (Case Studies in Construction Materials)
Strengthening reinforced concrete (RC) beams often face challenges, such as the brittleness of adopted materials and adhesive degradation over time. This study investigates a new strengthening method using engineered cementitious composite (ECC) and steel wire (SW) to enhance the flexural performance of RC beams. To evaluate the effectiveness of the proposed method, four distinct strengthening configurations of RC beams were designed and tested to experimental testing. In addition, a finite element (FE) model was developed to analyze the working mechanisms of the ECC-SW strengthened beams. Moreover, a pre-damaged FE model was established to investigate the effect of the reinforcement layer on the performance of cracked RC beams. The experimental results indicate that the ECC-SW strengthening layer effectively limits crack widths in the soffit of RC beam, with increase the flexural capacity and stiffness by 15.1 % and 8.5 %, respectively. The FE analysis reveals that original cracks reduce the ultimate stress and strain of the strengthened RC beam. Under the pre-damage condition corresponding to 1/4 of the ultimate deflection, the flexural capacity of beam strengthened with the ECC-SW composite layer only decreases by 4.9 %. This study provides valuable insights for the design and strengthening of RC beams. flexural capacity